Comparison of climate change causes of flood disaster adaptation strategies in Tanzania and Indonesia - Octaviana, Indra Saktia; Koestoer, Raldi Hendro (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Floods are one type of disaster triggered by climate change that occurs globally. Many cities in the world have responded to combat climate change by establishing a number of action plans to combat climate change, including the City of Dar Es Salaam in Tanzania and the City of Jakarta in Indonesia. The aim of this study is to review and compare adaptation strategies to combat climate change established by the City of Dar Es Salaam and the City of Jakarta based on research conducted in 2022-2023 and other relevant literature. The method used in this research is Systematic Literature Review (SLR) and comparative study with a qualitative descriptive approach to the evaluation of climate change induced flood disaster adaptation strategies between Dar Es Salaam, Tanzania and Jakarta, Indonesia. Study shows that the adaptation programs implemented in Dar Es Salaam and Jakarta have generally similar programs. Both cities have a number of programs that describe adaptation strategies for potential flood disasters induced by climate change which in this study grouped into seven aspects. However, the Dar Es Salaam City program still tends to focus on the institutional level (institutional wise) while the Jakarta program has started to focus on a community basis (community wise) which is starting to involve and develop the community in the climate change action plan program. It is highly recommended for the city of Dar Es Salaam to start changing the focus of its adaptation strategy to be more community-based to increase community ownership of the strategies that would be implemented.